Рахмановтың «Ақыбет» романында фразеологизмлердиң қолланылыў өз- гешеликлери - Досжанова, Г.Д. К (SCIENCE and SOCIETY, 2017)
The article is devoted to the study of phraseologisms used in the novel “Akibet” by K.Rakhmanov. The author of the article anal- yses peculiarities of using pharaseological synonyms and variants.
Keywords: phraseologism; pharaseological synonym; synonym; pharaseological variant; semantic; vocabulary; lexical variant; grammatical variant